2004
DOI: 10.1002/ejic.200300157
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Catalase Activity of Dinuclear Manganese Complexes by Utilizing Different Substituted Tripodal Ligands

Abstract: A series of five new dinuclear manganese(II/II) compounds with derivatives of 2-{[bis(pyridin-2-ylmethyl)amino]-methyl}phenol (HL 1 ) were synthesized and structurally characterized. All complexes crystallize in monoclinic space groups and exhibit Mn···Mn separations in the range of 3.392(8)−3.493(2) Å caused by bis(µ-phenoxo) bridging modes. The derivatives of HL 1 contain either electron-donating or -withdrawing substituents. A correlation between the electronic character of the different ring substituents, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 39 publications
7
26
0
Order By: Relevance
“…The secondary amine precursors to 2 and 3 were prepared by following a procedure for a similar compound,54 although the yields were unexpectedly low, there being at least one other major, unidentified product in each case. Diethylamine is commercially available and the target DEA-DCF was synthesized in adequate yield (52 %) and excellent purity.…”
Section: Resultsmentioning
confidence: 99%
“…The secondary amine precursors to 2 and 3 were prepared by following a procedure for a similar compound,54 although the yields were unexpectedly low, there being at least one other major, unidentified product in each case. Diethylamine is commercially available and the target DEA-DCF was synthesized in adequate yield (52 %) and excellent purity.…”
Section: Resultsmentioning
confidence: 99%
“…Although the structure of these enzymes has been determined, their catalytic mechanism is still poorly understood and the functional role of the bridges is yet unclear. Owing to their potential application as therapeutic agents against oxidative stress and as catalysts for bleaching and organic chemistry, a large number of dinuclear manganese complexes including various types of ligands have been synthesized and structurally characterized and many model complexes have been reported that show catalase activity [9][10][11][12][13][14][15][16]. An exhaustive and comprehensive review of the relevant research has recently been made [17].…”
Section: Introductionmentioning
confidence: 99%
“…The present system also gives higher catalytic efficiency than the recently reported [Mn 2 (L) 2 Cl 2 ] system {L ϭ 2-[bis(pyridin-2-ylmethyl)aminomethyl]-6-methoxyphenol}. [25] Eur. J. Inorg.…”
Section: Discussion and Comparison To Other Systemsmentioning
confidence: 67%
“…The total conversion of hydrogen peroxide disproportionation was measured using a manometric method, while the kinetic studies were performed on the basis of fluorescence quenching using an oxygen sensor. [11,25] The total catalytic activity as well as the rate of the reaction increases significantly when a few equivalents of NaOH are added. In Table 5 the turnover numbers for the disproportionation of H 2 O 2 by the manganese complexes in the presence and absence of NaOH are compared.…”
Section: Catalase Activity and Kineticsmentioning
confidence: 99%